650 POSTOPERATIVE EARLY ORAL FEEDING PROGRAM ACCELERATES THE RECOVERY OF GASTROINTESTINAL FUNCTION IN ESOPHAGEAL CANCER PATIENTS. (17th September 2021) - Wang, Peiyu; Chen, Xiankai; Li, Yin; Liu, Xianben
Abstract:  : Although the early oral feeding program (EOF) pasting the esophagectomy has been demonstrated to be valuable in attenuating inflammatory responses and shortening hospital stay without increasing complications, its impacts on gastrointestinal function recovery have not been elegantly investigated. This study aimed to solve these issues. Methods: A total of 110 esophageal cancer patients were included after reviewing a prospective database. Patients of EOF group were compared with patients of late oral feeding (LOF) group with respects to the appearance of first flatus and bowel movement after esophagectomy. Perioperative changes in serum gastrointestinal hormones were compared between EOF group and LOF group using variance analysis of repeated measurements. Multivariable logistic regression was conducted to detect risk factors for delayed recovery of gastrointestinal function after esophagectomy. Results: Patients of EOF group showed significantly shorter time from the surgery to the appearance of first flatus (2.1 ± 0.8 d vs 3.4 ± 1.2 d, P < 0.001) and bowel movement (3.2 ± 0.9 d vs. 5.5 ± 1.5 d, P < 0.001) than those of LOF group. Patients of EOF showed increased levels of serum gastrin (P = 0.007) and motilin (P = 0.027) but decreased levels of somatostatin (P = 0.004) and cholecystokinin (P = 0.028) than patients of LOF group based on the repeated measurements on postoperative day 1, 3, and 5. Multivariable analysis demonstrated the EOF (vs. LOF) as a protective factor for delayed recovery of gastrointestinal function. Conclusion: The postoperative EOF was demonstrated to accelerate the recovery of gastrointestinal function in esophageal cancer patients from the levels of clinical manifestation and hormone secretion. The EOF was anticipated to be highlighted in promoting perioperative managements.